Soul Management: A New Islamic Based Human Resource Development Model For Organizational Success - Khan, Shahid (2020)
Today, many organizations are facing a number of work ethic issues that violate work ethic such as corruption, fraud, dishonesty, disloyalty, selfishness, financial greed, careless, leakage of classified information, employee favouritism and misuse of improvisational resources. These unethical behaviors consequently will impede growth and threaten organizations with failure. Past researches claimed that unethical behaviour have a relation to the spiritual quality of the employee. Therefore, this study is exploring spirituality of employee in the aspect of spiritual “soul” and the values of Sincerity, Optimization of effort, Ultimate goal and Law compliance practices of the employee in the organization. Data were collected using purposive sampling technique with semi-structured interview questions. This study used open-ended in-depth interview method to explore the opinion of twelve executives from four different sectors which were Education, Health, Banking and Religious Affairs. Thematic analysis using NVivo 12 was used to analyse the data. Results of the study with the support from the literature review finally proposes that Sincere act, Optimization of effort, Ultimate goal and Law compliance (SOUL) as a new management which will enable the organization to develop the manpower holistically in the aspect of IQ, EQ and SQ. SOUL management model is expected to be very useful for all kind of organizations and industries.